The International Association for the Study of Lung Cancer/the International Thymic Malignancies Interest Group proposal for the TNM staging systems for thymic epithelial tumors and large-scale retrospective data - Kondo, Kazuya (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Thymic epithelial tumors are rare tumors. However, they are the most common tumor of the anterior mediastinum (1). A lot of studies analyzed retrospective clinical data of patients with thymoma from single-institute (2). Recently some studies analyzed large-scale retrospective clinical data (more than 1,000 patients) of thymic epithelial tumors including thymoma and thymic carcinoma from multiple institutes (3-5). The studies in Japan analyzed 1,320 patients with thymic epithelial tumors treated surgically from 115 institutes during the period from 1990 through 1994 and 2,835 patients with thymic epithelial tumors treated surgically during the period from 1991 through 2010 (3,4).